Dimensi Moral dan Spiritual dalam Satua Pamargan Ida Batur Taskara: Kajian Sastra Bali Purwa - Cahyani, Ni Luh Cesya Regita; Putriyani Dewi, Ni Luh PT.; Ardina Febrianti, Ni Komang; Sara Setyawati, Ni Made; Vika Tekendari, Ni Kadek Ayu; Santika Putra, I Made Agus; Juliartha, I Komang Trisna (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
This article examines the Satua Bali Purwa entitled “Pamargan Ida Batur Taskara.” This traditional Balinese literary work embodies profound moral, social, and spiritual values that remain relevant to contemporary life. The study aims to identify and analyze the intrinsic elements as well as the moral and spiritual dimensions contained within the satua, while also revealing the Hindu religious teachings and values underlying its formation. Intrinsically, the main theme centers on repentance and the law of Karma Phala, narrating the spiritual journey of Batur Taskara a character who initially lived in wrongdoing and chaos, but later attained self-awareness and purification of the soul. The plot develops progressively, illustrating the transformation of the protagonist. Extrinsically, the story reflects the worldview of Balinese society rooted in Hindu philosophy, encompassing the values of Tri Hita Karana, Catur Marga Yoga, Sad Ripu, and Karma Phala. Through these teachings, the work emphasizes the importance of maintaining harmony between human beings and God (Parhyangan), among fellow humans (Pawongan), and with the natural environment (Palemahan), as well as the need for self-control over worldly desires and passions. The moral and religious values embedded in this satua not only mirror the spiritual life of Balinese society but also serve as an effective medium for character education instilling virtue, honesty, and ethical awareness in future generations. Therefore, the study of Pamargan Ida Batur Taskara demonstrates that Satua Bali Purwa remains highly relevant in strengthening cultural identity, preserving Hindu teachings, and fostering noble character in facing the challenges of the modern era